2019
DOI: 10.3390/app9030486
|View full text |Cite
|
Sign up to set email alerts
|

Coded Excitation for Crosstalk Suppression in Multi-line Transmit Beamforming: Simulation Study and Experimental Validation

Abstract: (1) Background: Multi-line transmit (MLT) beamforming has been proposed for fast cardiac ultrasound imaging. While crosstalk between MLT beams could induce artifacts, a Tukey (α = 0.5)-Tukey (α = 0.5) transmit-receive (TT-) apodization can largely—but not completely—suppress this crosstalk. Coded excitation has been proposed for crosstalk suppression, but only for synthetic aperture imaging and multi-focal imaging on linear/convex arrays. The aim of this study was to investigate its (added) value to suppress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Clearly, because only a fraction of the lines beam‐formed by MV will have this artifact, and the rest of the lines formed by DCT‐based reconstruction are without this type of artifact, the MV+DCT exhibits a lower level of these artifacts. Also, some studies have used the Tukey filtering method to reduce this kind of artifact 35 . In this article, we used Savitzky‐Golay (SG) filtering to suppress the artifact from the RF signals 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, because only a fraction of the lines beam‐formed by MV will have this artifact, and the rest of the lines formed by DCT‐based reconstruction are without this type of artifact, the MV+DCT exhibits a lower level of these artifacts. Also, some studies have used the Tukey filtering method to reduce this kind of artifact 35 . In this article, we used Savitzky‐Golay (SG) filtering to suppress the artifact from the RF signals 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, for 256-element layouts the SNR is expected to drop down by 18dB, while for PA+PB the reduction is expected to be 9dB [45]. In general, limited CR and resolution can be improved by employing advanced imaging techniques such as: image coherent compounding, which, even if it limits the frame rate, has already been shown to be effective for cardiac applications based on the transmission of diverging waves [20], [21], [48]; coherence based beamforming methods in reception, enabling both improved spatial resolution and contrast [49]- [52]; adaptive and minimum variance beamformers for artifacts rejection [53]- [56]; the transmission of coded signals for the suppression of cross-talk artifacts in multiline transmission imaging [57], [58]. Also, we showed that mixed array configurations, compared to single array configurations, have a positive impact on CR; nevertheless, a further improvement could be achieved by optimizing the selection of active elements to be assigned to the transmitting and to the receiving arrays [46], [47], [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, the improvement of temporal resolution comes at the expense of image quality, thus pushing researchers to recover it by developing smart strategies. Four papers have been published in this Special Issue presenting advanced transmission sequences [7,8] and beamforming schemes [9,10] applied to either plane waves [7,10] or multi-line transmission imaging [8,9].…”
Section: Novel Beamforming Techniquesmentioning
confidence: 99%
“…Additionally, they showed that the use of non-uniform angle sets is a smart solution to keep the frame rate high, while limiting the level of image artifacts due to grating lobes. Tong et al [8] studied the effectiveness of orthogonal coded excitations in multi-line transmission imaging in suppressing crosstalk artifacts. They showed that Golay codes enable higher crosstalk rejection (and better contrast) compared to linear chirps.…”
Section: Novel Beamforming Techniquesmentioning
confidence: 99%